Strong adsorption of CV dye by Ni ferrite nanoparticles for waste water purification: Fits well the pseudo second order kinetic and Freundlich isotherm model - Debnath, Simi; Das, Ratan (Ceramics international, 2023)
This work focuses on the crystal violet (CV) dye removal from water by using prepared spherical and crystalline nickel ferrite nanoparticles (NiF-NPs) having cubic spinel phase with average size of 28 nm. The toxic, carcinogenic and mutagenic nature of CV dye along with long time persistence in the environment without degradation causes a major impact on living organisms and hence, the removal of CV dye from drinking water is necessary. The experimental batch adsorption data have been analyzed through Langmuir, Freundlich, Temkin and Dubinin-Radushkevich isotherm models. It is observed that the data fits well in the Freundlich isotherm model as correlation coefficient value (R2) is 0.985, which indicates formation of multilayer coverage over the surface of NiF nanoparticles. Again, Dubinin-Radushkevich's model has provided the adsorption energy (E) of CV dye as 1.629 (kJ/mol), which indicates that dye adsorption takes place through the physical-sorption process. Further, kinetic study indicates that the pseudo 2nd order model is suitable for adsorption data as equilibrium adsorption capacity has been found as 19.58 (mg/g) and R2 value as 0.998 with low value of rate constant (k2) as 0.019 (g mg−1 min−1). Further, R2 value for intra-particle diffusion model is obtained as 0.999, hence it is suitable for explaining the mechanism of adsorption process.